2010
DOI: 10.1177/0042098009359953
|View full text |Cite
|
Sign up to set email alerts
|

Marshall’s Scale Economies and Jacobs’ Externality in Korea: the Role of Age, Size and the Legal Form of Organisation of Establishments

Abstract: This paper revisits the concept of agglomeration economies by estimating the effects of localisation, urbanisation and local competition on labour productivity using establishment-level data in Korean manufacturing industries. It is found that, when an establishment locates in a more localised/specialised, more urbanised/diversified and more competitive area, its workers become more productive due to external benefits from agglomeration. Issues of self-selection bias and omitted variable bias are addressed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Through this finding, it was possible to explain the properties of the industries receiving more external costs from large areas and diversified environments. The failure of transport industries to absorb external benefits from any agglomeration economies source is contrary to the conclusions from Lee et al (2010) and Henderson et al (2001). They studied the same industry in Korea and found that it sourced external benefits from localisation.…”
Section: )mentioning
confidence: 90%
See 1 more Smart Citation
“…Through this finding, it was possible to explain the properties of the industries receiving more external costs from large areas and diversified environments. The failure of transport industries to absorb external benefits from any agglomeration economies source is contrary to the conclusions from Lee et al (2010) and Henderson et al (2001). They studied the same industry in Korea and found that it sourced external benefits from localisation.…”
Section: )mentioning
confidence: 90%
“…Nevertheless, when compared to localisation economies in other countries' cases, our result apparently exhibited a similar magnitude. These include the 0.02 to 0.08 for the United States manufacturing (Henderson 2003), 0.03 for British manufacturing (Graham 2009), 0.032-0.063 for Korean manufacturing (Lee et al 2010), and 0.05-0.06 for French manufacturing (Martin et al 2011). This finding contradicts the survey of De Groot et al ( 2016) that conclude it would be a less likely insignificant effect of specialisation when using micro-panel data as it might be less important at the firm level.…”
Section: Aggregate Estimatementioning
confidence: 99%
“…This conceptualization formalizes the importance of both scale economies, internal to the firm and captured by size, and agglomeration economies (Song Lee et al 2010), which capture the external benefits of the agglomeration of production activities in urban areas. The model also allows accounting for both MAR-and Jacobs-type agglomeration economies (Marshall 1890;Arrow 1962;Romer 1986;Jacobs 1969).…”
Section: Empirical Model and Datamentioning
confidence: 99%